THE IMPACT OF CAPITAL ADEQUACY, EFFICIENCY, SIZE, EQUITY, LIQUIDITY AND FEE BASED INCOME TO BEHAVIOR OF FUNDING AND FINANCING OF ISLAMIC BANKING IN INDONESIA - Adlina, Hannina; Arfianto, Erman Denny (Diponegoro Journal of Management, 2016)
Bank as the financial intermediary institution take a role to facilitate the channeling between the parties who have excessive fund and distribute to the parties who need fund. This study aimed to see the implication of CAR, efficiency, size, equity, liquidity and fee based income to the behavior of funding and financing. This study used Â Data Envelopment Analysis to measure efficiency value through intermediary approach and Multiple Regression Analysis. The samples are 11 Islamic Banks listed in Financial Service Authority database in years period January 2010 until December 2014. The result indicates that CAR has positive and significant impact to funding behavior, however some other determinants such as efficiency, asset, equity, liquidity and fee based income do not affect funding behavior. Meanwhile asset and liquidity has positive and significant impact to financing, equity has negative impact to financing, however other determinants such as CAR, efficiency and fee based income do not affect financing behavior.